Children's Experience of Sport: What Do We Really Know?. Issue 3 (2nd July 2016) - McPherson, Lynne; Atkins, Prue; Cameron, Nadine; Long, Maureen; Nicholson, Matthew; Morris, Meg E.
Abstract: Internationally, children's participation in leisure activities, including sport, is considered to be of such importance that it is enshrined as a human right. However, there is a growing awareness that children's experience of sport is not always benign; abuse and harm frequently occur within a broad range of organised sport contexts. This systematic literature review examines the international research evidence from both peer reviewed and grey literature on the abuse and harm of children that can occur in sport. Four areas of focus were apparent in this literature: first, types of abuse encountered by children in sport and the harm caused to them; second, persons responsible for the abuse and harm; third, circumstances under which children may be most vulnerable; and fourth, the role that culture plays in facilitating abuse in sport. The paper concludes identifying the need for further research in this domain.